ID: 14. Issue 1 (November 2015) - Artis, David
<x xml:space="preserve">Abstract</x> Employing models of microbial colonization, pathogen infection, chronic inflammation and tissue repair, research in the Artis lab is examining how mammalian host genetics and signals derived from the environment and commensal microbial communities influence innate and adaptive immune cell responses. We are employing gnotobiotic mice to examine the influence of defined commensal microbial communities on intestinal and peripheral immune cell development, function and influence on tissue homeostasis. Our recent findings indicate that commensal microbes have a significant regulatory influence on lymphocyte, innate lymphoid cell and granulocyte function associated with susceptibility to multiple infectious, inflammatory and metabolic disease processes. It is hoped that the results of these studies will advance understanding of the pathophysiology of multiple chronic inflammatory diseases, including asthma, allergy, inflammatory bowel disease and obesity, and provide a framework to test new therapeutic pathways to prevent and treat these diseases.